Compression in image recovery watermarking using PNG (Portable Network Graphic) - Chang, Billy Zhi Yang (2013)
Medical image is a very important material in medical world. A medical image is able to control and judge a life of human. Therefore the messages that keep inside the medical image must be protect well to avoid tragedy. Watermarking is a process that back up and protect the information of the in the medical image. An image is divided into two parts ROI (Region of Interest) which is an area that holding important process and RONI (Region of Non Interest) which is the area that is black in color in the medical image. In the process of watermark, all the information is compressed to reduce the size for storing purpose. Compression method plays a role in watermark process. Once the capacity of storage is limited, the smaller the size the information, the more information can be store. Lossless compression method is the first choice for the research due to same quality of the image will be produce after compressed. The type of lossless compression method will be tested and the better compression method which is holding the lowest value of compression ratio will be chose. TALLOR (Tamper Localization and Lossless Recovery) is use in the research. The important information in ROI will be compressed and embed in RONI. After the process of embedding is end, the watermarked image is tested with the PSNR (peak signal-to-noise ratio) to calculate the similarity of the image before and after watermarked. A high value of PSNR value is preferred which is in the range of 35.0 dB to 55.dB.